2019
DOI: 10.3390/ijms20020310
|View full text |Cite
|
Sign up to set email alerts
|

p21WAF1/Cip1 Regulation by hYSK1 Activates SP-1 Transcription Factor and Increases MMP-2 Expression under Hypoxic Conditions

Abstract: The hYSK1, a serine/threonine kinase (STK)-25, has been implicated in a variety of cellular functions including cell migration and polarity. We have recently reported that hYSK1 down-regulated the expression and functions of p16INK4a, a cell cycle regulatory protein, thereby enhancing migration and growth of cancer cells under hypoxic conditions. In this study, we further investigated the mechanisms underlying downregulation of p16INK4a and anti-migratory function of hYSK1. Our study revealed that p21WAF1/Cip1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 25 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…19 Lee et al revealed that STK25 increased cancer cells proliferation and migration under hypoxic condition through the interaction of STK25 with p21 WAF1/Cip1 to inhibit p16 INK4a promoter activity and increase the expression of MMP-2. 20 However, Lim et al suggested that loss of STK25 promoted the proliferation of tumor cells through the inactivation of the Hippo signaling pathway. 21 Patients with high STK25 expression in neuroblastoma are correlated with a favorable prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…19 Lee et al revealed that STK25 increased cancer cells proliferation and migration under hypoxic condition through the interaction of STK25 with p21 WAF1/Cip1 to inhibit p16 INK4a promoter activity and increase the expression of MMP-2. 20 However, Lim et al suggested that loss of STK25 promoted the proliferation of tumor cells through the inactivation of the Hippo signaling pathway. 21 Patients with high STK25 expression in neuroblastoma are correlated with a favorable prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Zhang et al demonstrated higher STK25 expression in prostate cancer tissues than in benign prostatic hyperplasia, which is involved in prostate tumorigenesis 19 . Lee et al revealed that STK25 increased cancer cells proliferation and migration under hypoxic condition through the interaction of STK25 with p21 WAF1/Cip1 to inhibit p16 INK4a promoter activity and increase the expression of MMP‐2 20 . However, Lim et al suggested that loss of STK25 promoted the proliferation of tumor cells through the inactivation of the Hippo signaling pathway 21 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, STK25 seems to have distinctly different functions in stressed cells and non-stressed cells, regulating cell death of the former [11]. Lee et al [12] reported that STK25 suppresses the expression and function of p16 INK4a , a cell cycle regulatory protein, thereby increasing the migration and proliferation of cancer cells under hypoxic conditions.…”
Section: Stk25 and Cell Polarity/apoptosis/migrationmentioning
confidence: 99%